Investigation of the effect of temperature and pretreatment on the rehydration capacities of dried nectarine slices - Soysal, Fatma; Ismail, Osman (UNIV ESTADUAL MARINGA, PRO-REITORIA PESQUISA POS-GRADUACAO, 2017)
In this study, the effect of temperature and pretreatment on the rehydration capacity of nectarine slices dried either with pretreatment and under ambient conditions (natural') at 50 degrees C in a cabinet dryer was investigated. Rehydration proceeded with distilled water at three different rehydration temperatures (25, 50, and 75 degrees C). Initial rehydration rates increased with rehydration temperature for all samples and were highest for the potassium carbonate (potas)-pretreated samples. At all rehydration temperatures, the equilibrium moisture content was highest for those pretreated with potas solution. The values of D-eff varied from 2.79 to 4.32x10(-10), 1.72 to 2.34x10(-10), and 1.86 to 2.58x10(-10) m(2) s(-1) for potassium carbonate, citric acid, and natural samples, respectively. The activation energy values were 5.65, 6.06, and 8.29 kJmol(-1) for citric acid, natural, and potassium carbonate nectarine slices, respectively. The rehydration data were fitted to Peleg and first-order kinetic models: the first order kinetic model was found to be the most appropriate model for rehydration of nectarine slices.
Keywords: rehydration curves; pretreatment; effective diffusivity; mathematical models; BEANS PHASEOLUS-VULGARIS; WATER-ABSORPTION; POTATO CUBES; KINETICS; DEHYDRATION; HYDRATION; MOISTURE; SEEDS; Science & Technology - Other Topics